Provision of Clean Energy and Cheap Energy Conservation in Islamic Boarding Schools - Hendra Jonathan Djayani Marentek; Toni Kurnia Jaya; Ismail Hasan (AMUYA: JOURNAL OF MANAGEMENT, 2025)
This paper describes that Islamic boarding schools in Indonesia in 2024 will reach 36,600 boarding schools, with a total of 3,642,738 students, which is a potential market share as well as a potential target to be developed into a clean energy manufacturing provider as well as an energy conservation area. On the other hand, the Indonesian Government is trying to increase the portion of the renewable energy mix according to the National Energy Policy (KEN) which will reach 23% in 2025. Islamic boarding schools as one of the centers of educated people are the right place to socialize and implement the New Renewable Energy and Energy Conservation program. The purpose of this study is to calculate the technical feasibility of utilizing communal biogas for cooking, generating rooftop solar power to support the energy diversification program and reduce PLN electricity bills, and replacing LED lamps according to SNI 6197:2011 concerning lighting systems in building structures and supporting energy conservation efforts. The methodology used is a survey and direct measurement related to local solar energy potential, the precision of the PLTS location, electricity needs, biogas potential and its designation, and lighting needs. Data processing was carried out using Meteonom, CorelDraw, and Pvsyt software. The results of the study showed that, for example, the Al Ihsan Islamic Boarding School case, is worthy of being recommended as a pilot project for the program. PP Al Ihsan has a potential for solar radiation of 4.91 kWh/m2.day with an average annual temperature of 27.8 oC so it is feasible to build a rooftop PLTS with a capacity of 13,000 Wp to supply the electricity needs of the boarding school which reaches 15,840 VA. The number of students of PP Al Ihsan which reaches 590 students with a sufficient area makes PP Al Ihsan feasible to build a communal biogas with a scale of 6 m3. In terms of replacing LED lamps, PP Al Ihsan will meet SNI standards by replacing 39 5-watt LED lamps, 89 13-watt LED lamps, and 18 27-watt LED lamps.